2013
DOI: 10.1002/sce.21078
|View full text |Cite
|
Sign up to set email alerts
|

Science Instructional Time Is Declining in Elementary Schools: What Are the Implications for Student Achievement and Closing the Gap?

Abstract: Recent comparative data on high school graduates show that many American students are not well prepared in fields of science, technology, engineering, and mathematics and that there is a persistent achievement gap according to the socioeconomic backgrounds of students. The research for this paper focuses on the role of elementary education in science as an important preparatory step. National trend data show a decline in instructional time in the elementary grades on science instruction over the past two decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 10 publications
1
65
0
Order By: Relevance
“…This study illustrates how engineering design and reading comprehension strategies may share points of overlap as well. On a practical level, this study has implications for the many elementary teachers who want to integrate more science and engineering concepts into their curriculum but feel pressed for time (Blank, 2013). Although our instruction in the literacy block focused heavily on teacher modeling and student practice with comprehension strategies, we found that students who applied these comprehension strategies were usually also engaging in engineering design processes.…”
Section: Discussionmentioning
confidence: 85%
“…This study illustrates how engineering design and reading comprehension strategies may share points of overlap as well. On a practical level, this study has implications for the many elementary teachers who want to integrate more science and engineering concepts into their curriculum but feel pressed for time (Blank, 2013). Although our instruction in the literacy block focused heavily on teacher modeling and student practice with comprehension strategies, we found that students who applied these comprehension strategies were usually also engaging in engineering design processes.…”
Section: Discussionmentioning
confidence: 85%
“…Yet, science instruction receives less instructional time than other subjects at the elementary school level (Blank, 2013). Further, elementary school teachers report feeling unqualified to teach science (Sandholtz & Ringstaff, 2014).…”
Section: Finding 3: Concerns About Student Preparationmentioning
confidence: 99%
“…Currently, vast differences exist between schools in the amount and quality of science instruction (Douville, Puglee, & Wallace, 2003;Duschl et al, 2007;Blank, 2013). In order to be successful under the NGSS, students need consistent exposure to highquality, NGSS-aligned science instruction beginning in kindergarten and continuing all through their schooling.…”
Section: Implications For Policymentioning
confidence: 99%
“…The justification for research on the impact of adequate resources for elementary science instruction is based on the numerous federal reports over the past decade that call for an increase in science education, both in time and quality in an attempt to improve the STEM workforce in the United States (Holdren, Marrett, & Suresh, 2013;NRC, 2009) Language Arts (ELA) and less than half the amount of time spent on mathematics (Blank, 2013).…”
Section: Significance Of the Research Problemmentioning
confidence: 99%
“…Since 2000, the instructional time spent on elementary science education has declined while time on ELA and mathematics has increased (Blank, 2013).…”
Section: Increasing Time and Attention Dedicated To Sciencementioning
confidence: 99%